2021
DOI: 10.1039/d1se00697e
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a hierarchically structured, NiCo–Cu-based trifunctional electrocatalyst for efficient overall water splitting and 5-hydroxymethylfurfural oxidation

Abstract: In this study, Cu nanowire arrays grown on a three-dimensional Cu foam substrate are modified by nickel-cobalt layered double hydroxide nanosheets (NiCoNSs/CuNWs), which can be used as a self-supporting trifunctional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 48 publications
1
17
0
1
Order By: Relevance
“…The MoO 2 –FeP@C||MoO 2 –FeP@C electrolyzer afforded a voltage of 1.486 V at 10 mA cm −2 for simultaneously generation of FDCA H 2 . [ 28 ] Other catalysts such as NiSe@NiO x core–shell nanowires, [ 62 ] Mo‐doped Ni 0.85 Se on nickel foam (NF@Mo–Ni 0.85 Se), [ 31 ] Cu x S@NiCo‐LDHs core–shell nanoarray, [ 61 ] and nickel‐cobalt‐layered double‐hydroxide NSs modifying Cu nanowire arrays on Cu foam (NiCo NSs /Cu NWs ) [ 65 ] were also reported in the HMF electrolysis system which shows desirable catalytic performance ( Table 4 ).…”
Section: Organic Eor Assisted With Her For H2 Generationmentioning
confidence: 99%
“…The MoO 2 –FeP@C||MoO 2 –FeP@C electrolyzer afforded a voltage of 1.486 V at 10 mA cm −2 for simultaneously generation of FDCA H 2 . [ 28 ] Other catalysts such as NiSe@NiO x core–shell nanowires, [ 62 ] Mo‐doped Ni 0.85 Se on nickel foam (NF@Mo–Ni 0.85 Se), [ 31 ] Cu x S@NiCo‐LDHs core–shell nanoarray, [ 61 ] and nickel‐cobalt‐layered double‐hydroxide NSs modifying Cu nanowire arrays on Cu foam (NiCo NSs /Cu NWs ) [ 65 ] were also reported in the HMF electrolysis system which shows desirable catalytic performance ( Table 4 ).…”
Section: Organic Eor Assisted With Her For H2 Generationmentioning
confidence: 99%
“…For example, Ni generally offers high currents, while Co lowers the onset potential (usually the onset potential of precious metals is also very low) [62] . Consequently, NiCo alloys achieve low onset potentials and large catalytic currents, thus boosting the oxidation efficiency of HMF [63] . Apart from that, many studies have revealed that Au catalysts are more efficient for the oxidation of aldehyde groups with desirable selectivity, but Au may be deactivated more easily by the formed organic products [64] .…”
Section: Alloy Nanostructure Modulation For Electrocatalytic Hmf Oxid...mentioning
confidence: 99%
“…[62] Consequently, NiCo alloys achieve low onset potentials and large catalytic currents, thus boosting the oxidation efficiency of HMF. [63] Apart from that, many studies have revealed that Au catalysts are more efficient for the oxidation of aldehyde groups with desirable selectivity, but Au may be deactivated more easily by the formed organic products. [64] Instead, Pt and Pd catalysts are more efficient for the oxidation of alcohol groups, and they can keep Au stable.…”
Section: Alloy Nanostructure Modulation For Electrocatalytic Hmf Oxid...mentioning
confidence: 99%
See 1 more Smart Citation
“…[71] Sun et al integrierten die HMF-Umwandlung und H 2 -Entwicklung in 1.0 M KOH auf bifunktio-nalen Elektrokatalysatoren, wie CoP, [50] Ni 2 P [55] und Ni 3 S 2 , [56] wodurch die Produktion von FDCA und H 2 mit hohen FEs realisiert wurde. Andere bifunktionale Elektrokatalysatoren, wie Co-NW/NF, [72] MoO 2 -FeP@C, [61] NiSe@NiO x -NWs, [73] Cu x S@NiCo-LDHs, [74] NF@Mo-Ni 0.85 Se, [75] NiCo-LDH NiCo NSs/ Cu NWs [76] und Ni 3 N@C, [45] wurden ebenfalls für die Hybridelektrokatalyse beschrieben. Bei den oben stellvertretend genannten Elektrokatalysatoren folgen die Alkohol-und Aldehydumwandlungen in der Regel dem intramolekularen Mechanismus der Elektrooxidation in alkalischen Medien, bei dem eine starke Wechselwirkung zwischen dem organischen Substrat und der Elektrodenoberfläche besteht.…”
Section: Elektrooxidation Von Aldehydenunclassified